Sparkol Videoscribe berbasis Pemahaman Konsep Matematis: Sebuah Pendekatan Inovatif - Widyawati, Santi; Rosyidah, Ummi; Qomariyah, Siti; Setyawati, Astri (JEMS: Jurnal Edukasi Matematika dan Sains, 2023)
Numerous students encounter obstacles in comprehending the material of economic mathematics, suggesting a need for innovation in pedagogical approaches. In this context, the application of digital media, such as Sparkol Videoscribe-based instructional videos, presents a potential solution. The objective of this research is to construct and evaluate the efficacy of economic mathematics instructional videos utilizing the 4D (Define, Design, Develop, and Disseminate) development model. This study employs a Research and Development (R&D) approach, as well as the 4D development model. Validation tests involved subject matter experts, instructional design experts, and educational media experts. The effectiveness of the instructional videos was examined through individual trials, small group trials, and field testing. Findings from the reviews and trials demonstrated that the economic mathematics instructional videos were rated as outstanding, with validation percentages exceeding 90% in all categories. In field testing, the instructional videos received an excellent rating, with a percentage of 95.98%. The instructional videos significantly enhanced understanding of the concepts. This indicates that Sparkol Videoscribe-based instructional videos are effective in improving students' understanding of economic mathematics material. The research concludes that the construction and implementation of economic mathematics instructional videos using the 4D development model is effective in enhancing students' conceptual understanding. The study further provides recommendations for students, faculty, campuses, and other researchers to utilize and further develop digital educational media, such as videos, in the teaching and learning process.